Penerapan Algoritma VLBE Pada Aplikasi Kumpulan Cerita Rakyat Indonesia Berbasis Android - Sidabutar, Sarifah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The problem that occurs in the application of Indonesian folklore collection is the large number of stories stored causing the application size to be quite large and used to have a large memory space, but if the smartphone has a small memory space then it becomes a big enough problem.The application of a compression algorithm to the Indonesian folklore collection application will overcome the problem of application size and of course can display folklore so that children can recognize and understand folklore to reduce the record that will be compressed with the VLBE algorithm. Based on the application of the algorithm (VLBE), it has been proven that a folklore file that has a size with a large ratio of 50% can be compressed into smaller sizes. So that it can provide a faster process